The Influence Of Leadership And Physical Work Environment On Employee Performance At Alfamart Pamulang Area - Pratama, Ahmad Riyan; Gandung, Muhammad (Transforma Jurnal Manajemen, 2025)
The purpose of this study is to determine the influence of leadership and physical work environment on employee performance at Alfamart in the Pamulang Area, both partially and simultaneously. This research uses a quantitative method with an associative approach. The sample consists of 70 respondents, representing the entire employee population of Alfamart in the Pamulang Area, using a saturated sampling technique. Data collection was conducted through questionnaires and direct observation. The results show that leadership has a positive and significant effect on employee performance, as evidenced by the value of tcount > ttable (2.358 > 1.995) and Sig. < 0.05 (0.021). The physical work environment also has a positive and significant effect on employee performance with tcount > ttable (3.953 > 1.995) and Sig. < 0.05 (0.000). Simultaneously, leadership and physical work environment positively and significantly affect employee performance, as shown by Fcount > Ftable (25.343 > 3.134) and Sig. < 0.05 (0.000). This study indicates that improving the quality of leadership and physical work environment can enhance employee performance in modern retail environments such as Alfamart.